Study Of Bearing Capacity Of Piles Due To Vertical Loading In Pontianak - Saputra, Nanda Zulna; Bachtiar, Vivi; Priadi, Eka (Jurnal Teknik Sipil, 2025)
Infrastructure development in Pontianak, particularly the Kapuas Bridge Duplication Project 1 (MYC) 2022-2024, requires thorough foundation planning due to the area"™s soft, water-saturated soil with low bearing capacity. This study analyzes the ultimate bearing capacity (Qu) and settlement of 80 cm diameter steel pile foundations at pile point 3. The analysis reveals that the minimum pile bearing capacity (Qall) using the Brown (2001) method is 274,25 tons, while the APILE v.2019 program yields a bearing capacity of 383,3 tons. The group pile-bearing capacity analysis shows a total capacity of 2.875,511 tons, exceeding the applied working load of 2.683,304 tons, with a group efficiency of 0,699. The elastic settlement for a single pile is 3,87 mm, while the pile group"™s is 13,95 mm. Long-term consolidation settlement is calculated at 126,20 mm, while PLAXIS simulation results show 72,03 mm. Interpreting static load test results using various methods (Chin, Davisson, Meyerhof, etc.) shows variation in bearing capacity, with the Meyerhof method providing the most consistent results. Based on this analysis, the 80 cm diameter steel pile foundation meets the safety and stability requirements for long-term use.